2002
DOI: 10.1590/s0103-64402002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Submucous implant of abrasive dental materials in rat tongues: clinical and histological evaluation

Abstract: This study evaluated the clinical and histological manifestations produced by the submucuous implant of abrasive dental materials in the rat tongue. A total of 128 rats were divided into 4 groups of 32 rats each, according to the material selected for the implant: Herjos-F prophylactic paste both in its normal composition as well as lacking its abrasive components, SS White pumice stone and the abrasive powder of the 3M finishing and polishing sandpaper. The specimens were submitted to clinical and histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The presence of fibrous tissue, lymphocytes and giant cells suggest that the immune system recognize the PLLA-g-HA and PLLA/HA scaffolds similarly, and provoke the encapsulation of the material to try to phagocytize and degrade the implant. Some authors suggest that the presence of fibrous tissue in implanted materials does not always imply an incompatibility with the host tissues [7,8]. In our study it was observed the presence of fibrous tissue in all samples at different times of material extraction.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of fibrous tissue, lymphocytes and giant cells suggest that the immune system recognize the PLLA-g-HA and PLLA/HA scaffolds similarly, and provoke the encapsulation of the material to try to phagocytize and degrade the implant. Some authors suggest that the presence of fibrous tissue in implanted materials does not always imply an incompatibility with the host tissues [7,8]. In our study it was observed the presence of fibrous tissue in all samples at different times of material extraction.…”
Section: Resultssupporting
confidence: 61%
“…All experiments were approved by the Bioethics Committee of the Medicine and Psychology Faculty, Autonomous University of Baja California, Mexico, with registration number IORG # IORG007487, of United States Department of Health and Human Services (HHS). Also, the experiments were conducted in accordance with the Mexican Legislation Standard of NOM-063-SSA1-1993, Ley General de Salud [7].…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous publications there is strong evidence that PLLA/HA and PLLA/PLLA-g-HA scaffolds are biocompatible. Some authors suggest that the presence of granuloma in implanted materials does not always imply an incompatibility with the host tissues [7]. Such is the case of Branislav & Mirjana, who investigated the biocompatibility of different dental materials, intended for dental root canal obturation, by implantation in rat muscle tissue, through the analysis of different levels of inflammation of muscle tissue.…”
Section: Muscle Implantation Testmentioning
confidence: 99%
“…However, the cells do not possess the ability to grow in 3D orientations that define the anatomical shape of the tissue; instead, cells migrate to form random or two-dimensional (2D) layered fabrics. Despite this, the 3D structures are required, and this is accomplished by culturing the cells in three-dimensional porous structures known as "scaffolds", where the cells colonize and proliferate [7].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of adverse reactions for these products is still unknown. When exogenous materials are injected into tissues, a granulomatous reaction with the presence of macrophages and the formation of new collagen surrounding the area can be observed. It is known that, during the initial period (4–6 months after injection), the PMMA spheres provoke a foreign body reaction and are later encapsulated by the collagen fibres of the tissue.…”
Section: Introductionmentioning
confidence: 99%